Freeing Aspergillus fumigatus of Polymycovirus Infection Renders It More Resistant to Competition with Pseudomonas aeruginosa Due to Altered Iron-Acquiring Tactics - Patil, Rutuja H; Kotta-Loizou, Ioly; Palyzová, Andrea; Pluháček, Tomáš; Coutts, Robert H A; Stevens, David A; Havlíček, Vladimír (Journal of fungi (Basel, Switzerland), 2021)
A virus-free (VF) A. fumigatus isolate has been shown to be resistant in competition with Pseudomonas as compared to the isogenic line infected with Aspergillus fumigatus polymycovirus 1 (AfuPmV-1), and this phenotype was apparently related to alterations in iron metabolism. Here we investigated further the mechanisms underpinning this phenotype. The extracellular siderophore profiles of five isogenic VF and virus-infected (VI) strains were sampled at 24, 31, 48, 54, and 72 h in submerged cultures and quantitatively examined by liquid chromatography and mass spectrometry. Intracellular profiles of conidia and cultures at the stationary growth phase were defined. VF A. fumigatus demonstrated the best fitness represented by the fastest onset of its exponential growth when grown on an iron-limited mineral medium. The exponential phase and transitional production phase of the extracellular triacetylfusarinine C (TafC) were achieved at 24 and 31 h, respectively, contrary to VI strains, which acted more slowly. As a result, the TafC reservoir was consumed sooner in the VF strain. Additionally, the VF strain had lower ferricrocin and higher hydroxyferricrocin content in the pellet during the stationary phase. All of these differences were significant (Kruskal-Wallis, p < 0.01). In our study, the siderophore reservoir of a VF strain was consumed sooner, improving the fitness of the VF strain in competition with P. aeruginosa.
Keywords: Aspergillus fumigatus; polymycovirus; intermicrobial competition; Pseudomonas aeruginosa; siderophore